Debt default and democracy - edited by Giuseppe Eusepi (Cheltenham E. Elgar, 2018)
The original essays in this book connect the microeconomic and macroeconomic approaches to public debt. Through their thought-provoking views, leading scholars offer insights into the incentives that individuals and governments may have in resorting to public debt, thereby promoting a clearer understanding of its economic consequences.
Includes index.
Keywords: BUSINESS & ECONOMICS -- Public Finance; Debts, Public; Default (Finance); BUSINESS & ECONOMICS / Public Finance; Debts, Public; Default (Finance); Political economy